Building Citizen Satisfaction Towards E-Government Services: A Conceptual Framework - Telly Pauline Ulviana Siwi; Zaidan Nawawi (Universitas Padjadjaran, 2023)
In the context of government services, user satisfaction becomes the determinant of its success. This study aims to develop and examine a model for determining citizen satisfaction with e-government services using the technology acceptance model (TAM) and trust theory. Specifically, we look at the role of perceived e-service which consists of core services, facilitating services, and supporting services in influencing perceived usefulness and trust in e-government. We also see how trust in e-government affects perceived usefulness and citizen satisfaction. Finally, we examine perceived usefulness regarding its influence on citizen satisfaction. This study is carried out on citizens who are obliged to pay and report taxes (taxpayers) through the online platform of Directorate General of Taxes (DJP Online) in South Sumatera Province, Indonesia, as many as 240 respondents. The data is collected online by distributing questionnaires through Google Forms. The data obtained is then analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). The findings of this study indicate that perceived e-service which consists of core services, facilitating services, and supporting services has a positive influence on perceived usefulness and trust in e-government, while trust in e-government affects perceived usefulness and citizen satisfaction. Finally, this study confirms that citizen satisfaction is influenced by perceived usefulness.